2018
DOI: 10.1016/j.ajo.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antituberculous Therapy on Uveitis Associated With Latent Tuberculosis

Abstract: Treatment with ATT halved the risk of uveitis recurrence and delayed the onset of the first recurrence in eyes with uveitis associated with latent TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
(33 reference statements)
1
18
2
Order By: Relevance
“…Our survey also reaffirmed the role of ATT in the resolution of inflammation in intraocular TB. This has been described in a number of retrospective studies including recent multicentred trials, though the quality of evidence in this field is compromised by the lack of appropriate controls and grading of inflammation [ 8 , 9 ]. The participants also identified need for prolonged immunosuppression as a prognostic factor for the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey also reaffirmed the role of ATT in the resolution of inflammation in intraocular TB. This has been described in a number of retrospective studies including recent multicentred trials, though the quality of evidence in this field is compromised by the lack of appropriate controls and grading of inflammation [ 8 , 9 ]. The participants also identified need for prolonged immunosuppression as a prognostic factor for the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this study is the enumeration of prognostic factors for a disease, where such data are not available in current literature and would be difficult to derive directly from patient data. While recent multi-centre studies have attempted to evaluate prognostic factors for intraocular TB based on patient data, they have been limited by the lack of standardization, control groups and evaluation of individual phenotypes [ 8 , 9 ]. The modified Delphi technique used in this survey largely eliminated any bias or any dominating influence of individuals as typically occurs in face-to-face meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Various series have reported the use of oral corticosteroids along with ATT as a combination (oral prednisolone 1 mg/kg/ day) for IOTB with favorable control of inflammation [23,36,37,68,76,77,82]. Corticosteroids can be tapered over the next 6-12 weeks depending upon the severity of inflammation and occurrence of paradoxical worsening of the disease [83]. Certain authors favor the use of corticosteroids only when the lesions are involving or threatening the macula in order to decrease macular scarring [84].…”
Section: Managing Inflammation In Intraocular Tuberculosis-oral Cortimentioning
confidence: 99%
“…A meta-analysis has shown that 84% (95% CI 79–89) of the patients receiving ATT showed non-recurrence of inflammation during the follow-up period, 69% (95% CI 33–96) had an improvement in visual acuity, and 92% (95% CI 63–100) showed an improvement in inflammation [43]. In a cohort of patients attending uveitis clinics in London and Sydney, it was found that treatment with ATT halved the risk of uveitis recurrence and delayed the onset of the first recurrence in eyes with uveitis associated with latent TB [45].…”
Section: Introductionmentioning
confidence: 99%